Survey of diseases on Marula (Sclerocarya birrea), in Tshikundamalema, Limpopo Province, South Africa - Ramabulana, Elelwani (My University, 2016)
See the attached abstract below
MSCAGR (Plant Production)
Department of Plant Production
Keywords: Sclerocarya birrea; UCTD; DNA sequence data; Pathogenicity; ITS gene region; BT gene region; TEF gene region; RPB2 gene region; Fusarium; Lasiodiplodia; Macrophomina; 333.9532160968257; Anacardiaceae -- South Africa -- Limpopo; Biological diversity -- South Africa -- Limpopo; Plant species -- South Africa -- Limpopo